Impact of Screen Media Usage on Early Childhood Development - Malik, Muneeba; Maqbool, Shazia; Ali, Anam; Azhar, Hina; Ullah, Ehsan; Khan, Aisha Farid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To see the impact of screen media usage on early childhood development.Study Design: Cross-sectional study.Place and Duration of study: Developmental Behavioural Paediatrics Department, Children’s Hospital and Institute of Child Health, Lahore Pakistan, from Oct to Dec 2020.Methodology: This study included 100 children with an age range between 15-36 months and divided into two groups. Group-1 was children with communication behaviour disorders (CBD) (n=50), and Group-2 was typically developing (TD)children (n=50). ShaMaq Developmental Screening Tool (SDST) was administered to children to screen their development.Childhood behaviours were rated on a scale of 0-10 on a Behaviour rating scale.Results: Children with CBD had poor eye contact, response to names, poor imitation, poor pointing and poor one-step command following (p